Vertical Oscillation of a Simplified Model a Mechanical System - Soukup, Josef; Svoboda, Martin (Journal of Applied Nonlinear Dynamics, 2026)
This paper deals with vertical mechanical oscillation of symmetric and asymmetric systems with different kinematic excitation. The solution was carried out using numerical and experimental methods. The subject of analysis were the influence of geometry, production asymmetry and unbalanced excitation on the vibration of solid bodies in the system of flexibly bonded solids taking into account the boundary conditions and the type of loading (application to the oscillation of vehicles). Numerical solutions were performed using the ADAMS program. Experiments were performed on a laboratory model. The aim was to verify the applicability and suitability of different methods and procedures for the investigation of vertical oscillation of the mechanical system of bodies.